Improvement of phase change speed and thermal stability in Ge5Sb95/ZnSb multilayer thin films for phase change memory application. (23rd September 2019) - Zhao, Zihan; Hua, Sicong; Wu, Weihua; Shen, Bo; Zhai, Jiwei; Lai, Tianshu; Song, Sannian; Song, Zhitang
Abstract: Superlattice-like Ge5 Sb95 /ZnSb (SLL GS/ZS) thin films were fabricated by radio-frequency magnetron sputtering technology. [GS(4 nm)/ZS(10 nm)]4 thin films display excellent thermal stability, and their crystallization temperature, activation energy, and 10-year data retention temperature are 253 °C, 3.78 eV and 157 °C, respectively, which are higher than traditional Ge2 Sb2 Te5 (GST) thin films. Slight fluctuation (3.5%) in thin film volume during phase transition process indicates good reliability. Ultrafast crystallization speed (9.2 ns) in the [GS(4 nm)/ZS(10 nm)]4 thin film was validated, which contributes to accomplish rapid storage of data in phase change memory cell. Moreover, phase change memory cells based on [GS(4 nm)/ZS(10 nm)]4 thin films can achieve reversible SET and RESET operations with 20 ns width pulse.